Cluster Preface: Silicon in Synthesis and Catalysis - Oestreich, Martin (Synlett, 2017)
Martin Oestreich is Professor of Organic Chemistry at the Technische Universität Berlin. His appointment was supported by the Einstein Foundation Berlin. He received his diploma degree with Paul Knochel (Marburg, 1996) and his doctoral degree with Dieter Hoppe (Münster, 1999). After a two-year postdoctoral stint with Larry E. Overman (Irvine, 1999–2001), he completed his habilitation with Reinhard Brückner (Freiburg, 2001–2005) and was appointed as Professor of Organic Chemistry at the Westfälische Wilhelms-Universität Münster (2006–2011). He also held visiting positions at Cardiff University in Wales (2005) and at The Australian National University in Canberra (2010). Martin Oestreich’s research focuses on silicon in synthesis and catalysis, the theme of the present SYNLETT Cluster. His early work centered on the use of silicon-stereogenic silicon reagents in asymmetric catalysis, and his laboratory continues to employ them as stereochemical probes in mechanistic investigations. His research group made fundamental contributions to catalytic carbon–silicon bond formation with nucleophilic and, likewise, electrophilic silicon reagents, and Martin Oestreich is probably best known for his work in silylium-ion chemistry. Recent accomplishments of his laboratory include Friedel–Crafts-type C–H silylation, transfer hydrosilylation, and kinetic resolution of alcohols by enantioselective silylation.